ANALISA KAPABILITAS DINAMIS PADA PUSAT PELAYANAN TERPADU KEKERASAN PEREMPUAN DAN ANAK DI RUMAH SAKIT UMUM DAERAH TARAKAN DKI JAKARTA - , Dini Gandini Purbaningrum; Nida Handayani; Sokhivah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The Jakarta Provincial Government has Strategic Regional Policy number 13, focusing on Preventing and Addressing Violence against Women and Children. The policy's implementation occurs through the Tarakan Regional General Hospital (RSUD), which established the Bunga Tanjung innovation—a Health Service Center dedicated to women and children who are victims of violence. This center is managed comprehensively by medical staff and support personnel from RSUD Tarakan, collaborating with the Police and the Integrated Service Center for Women and Children Empowerment (P2TP2A). This research aims to understand and analyze the dynamic capabilities in managing the Health Service Center for victims of violence against women and children within the framework of Dynamic Governance proposed by Neo and Chen (2007), namely thinking ahead, thinking again, and thinking across. This research uses a descriptive qualitative approach. Determining the informants for this research used the Purposive Sampling Technique. The data collection method used interviews, observation and documentation. Data analysis techniques include: data collection, data reduction, data presentation and drawing conclusions. The research findings indicate that the thinking ahead capability is possessed by the administrators of PPT Bunga Tanjung, evident in several proactive initiatives to anticipate future challenges. However, there is still a need for improvement in the thinking again capability, requiring structured and periodic instruments to capture user feedback for formulating new strategies. The thinking across capability is practiced through benchmarking with a similar service called Sunflower in South Korea, adopting and adjusting services based on their model.